Barriers and facilitators for leading nursing homes through the COVID‐19 pandemic: A focus group study in Norway - Gro Beate Samdal; Lise‐Merete Alpers; Ragnhild Johanne Tveit Sekse; Sigrunn Drageset; Hilde Smith‐Strøm; Trine Oksholm; Sidsel Ellingsen (Wiley, 2023)
Abstract Background During the COVID‐19 pandemic, nursing home leaders implemented infection control to protect residents and staff. Aim To understand the barriers and facilitators for leading nursing homes through the COVID‐19 pandemic. Methods We invited 34 nursing homes to participate, and 20 leaders (59%) attended focus group interviews. The COM‐B model and the theoretical domains framework were used in design and analysis of the study. Results The barriers for infection control were organisational unpreparedness, high volumes of information, lack of clinical skills, protective equipment, and testing capacity, the nursing home's architectural design, health authorities' low priority of nursing homes, staff's fear, and mental pressure on the leaders over time. The facilitators were having a customised corona plan, change of routines, certification of new skills, access to the municipal quality system, the ability for crisis leadership, loyalty to the nursing home, and support from the environment. The number of part‐time positions and the opportunity to outsource parts of the services were also important determinants for infection control. Conclusions The results identify several barriers and facilitators for nursing home leaders' behaviour for infection control. The results confirm the importance of supporting the leaders' resilience and crisis leadership while working in the pressurised environment of a pandemic. Relevance to Clinical Practice The study provides important insights into barriers and facilitators for leading nursing homes through the COVID‐19 pandemic, which could help to inform future strategies for infection control. Patient or Public Contribution No patient or public contribution.